2012
DOI: 10.1002/app.38508
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of new AR glass fiber‐reinforced cements with potential medical applications

Abstract: The aim of this study was to obtain and investigate new biomedical glass fiber resin cements with improved mechanical properties and radiopacity, using alkaline-resistant (AR) glass fibers. New light-curing, self-curing, and dual-curing resin cements were obtained from AR glass fibers and BaSO 4 powder mixed with 2,2-bis[4-(2-hydroxy-3-methacryloyloxypropoxy)-phenyl]propane and triethyleneglycol dimethacrylate monomers at different weight ratios, such as 5/20/75, 10/20/70, 20/20/60. The newly obtained cements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
(59 reference statements)
4
4
0
Order By: Relevance
“…These results were in agreement with other studies regarding the stopping of crack propagation of glass/basalt fiber in composites [ 20 , 21 , 22 ]. In our study, unidirectional MiniBars™ showed higher mechanical properties than Fly100.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results were in agreement with other studies regarding the stopping of crack propagation of glass/basalt fiber in composites [ 20 , 21 , 22 ]. In our study, unidirectional MiniBars™ showed higher mechanical properties than Fly100.…”
Section: Resultssupporting
confidence: 93%
“…The flexural modulus of MiniBars™ FRBCs ( Figure 4 b) increased in the same way with the increased addition of MiniBars™: more than 3.33–5.92 times than that of Fly100, with values between 267.74–475.63 MPa. These results were in agreement with other studies when the addition of glass fiber increased mechanical properties and fibers acted as crack stoppers [ 19 , 20 , 21 , 22 ]. Under the load applied to MiniBars™ FRBC, the cracks will be bridged by MiniBars™.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The mechanical properties of FRCs depend on two main variables: the type of organic matrix [9,10], which gives the mechanical properties of the organic part [11,12], and the inorganic filler [13], characterized by the type, size, and geometry [13,14]. Other factors that influence the mechanical behavior of FRCs are the silanization [8], factors affecting the polymerization efficiency [15,16], and the binding between the inorganic filler and the organic matrix [8,17]. The clinical longevity of a dental material such as FRCs is correlated with the mechanical properties [18], because increased mechanical properties facilitate a good response to occlusal mechanical stress (clinical wear) [19].…”
Section: Introductionmentioning
confidence: 99%
“…After the first introduction of bioactive glasses by Hench et al, bioactive glasses have been a growing interest for implant application with ability to form a direct bond to living bone by forming a surface hydroxyapatite layer in physiological conditions [21][22][23]. There are now several types of bioactive glasses, including conventional silicate glass [24][25][26], phosphate-based glass [27][28][29][30], and borate-based glass [31][32][33].…”
Section: Introductionmentioning
confidence: 99%